PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR BIOLOGI SISWA - Rahimah Suling Allo; Nurul Fadhilah (UNIVERSITAS KHAIRUN, 2022)
Learning is basically a process of contact between teachers and students, both direct involvement, such as face-to-face activities, through the use of various learning models. The purpose of this study was to determine the effect of learning models flipped classroom on the results of studying biology on mushroom material for class X SMA Negeri 3 Gowa. This study is a pre-experimental designone-group pretest posttest design. The population in this study were all students of class X SMA Negeri 3 Gowa, totaling 162 people with the sample being class X MIA 3 with a total of 24 students. The research instrument used was a test of student learning outcomes. Data analysis techniques used two ways, namely descriptive and inferential data analysis techniques (normality test, homogeneity test and hypothesis testing). Test the hypothesis using independent sample t-test with the help of SPSS software version 25 with a significant value p = 0.000 0.05. Thus, it can be concluded that there is an influence of the learning model flipped classroom on the results of studying the biology of the mushroom concept in class X SMA Negeri 3 Gowa.